Role of perioperative Factor XIII in intracerebral hemorrhage after brain tumor surgery: A prospective study - Estela Val Jordan; Agustín Nebra Puertas; Juan Casado Pellejero; Lluis Servia Goixart; Jorge Rubio Ruiz; Silvia Rodriguez Ruiz; Neus Montserrat Ortiz; Gabriel Jimenez Jimenez; Concepción Revilla López; Nuria Fernández Monsteirín; Manuel Quintana Díaz; Jesús Caballero López (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2021)
Background: Intracerebral Hemorrhage (ICH) is one of the most feared complications after brain tumor surgery. Postoperative hemorrhage has been described in presence of a reduction of Factor XIII (FXIII) with normal routine coagulation tests in different fields. The primary objetive was to evaluate the influence of perioperative FXIII levels on ICH after brain surgery.  Methods: A prospective, observational, 18-month study was conducted at a third-level hospital in Spain. It included all consecutive adults (18 years of age or alder) operated on elective brain tumor surgery with postoperative stay in the Neurointensive Care Unit (N-ICU). Informed consent from all participants and ethical approval were obtained. Younger than 18 years of age, informed refusal, death in the OR, incomplete blood sample or non-tumoral tissue were exclusion criteria.  Three blood samples evaluated FXIII levels (A-presurgical, B-postsurgical and C-24 hours after surgery). ICH, as a primary outcome variable, was defined as bleeding that generates radiological signs of intracranial hypertension either by volume or by mass effect on the routine CT scan 24 hours after surgery. The influence of tumoral data and standard coagulation were also analized. Chi-square (χ2) and Fisher's exact tests, Mann-Whitney U and T-Tests and multiple regression were used for inferential analysis.  Results: The study included 109 patients. ICH was finally confirmed in 39 of them (35,78%). Inferential analisys determined statistical association between lenght of stay in ICU (p<0,01) and male group (p0,03) with ICH. The average of FXIII was lower in patients who suffered from ICH, specially in B sample (A 71,2%, B 51,57%, C 52,14%). Statistical analisys determined FXIII deficiency (FXIIID) (<70%) after brain tumor surgery increased ICH (A p0,073, B and C p<0,01). FXIII baseline variation was also associated to ICH (FXIII A-B and A-C p<0,01, FXIII B-C 0,282). However, standard coagulation was not associated with either ICH or FXIIID. Conclusion: Acquired FXIIID (<70%) after brain tumor surgery increased ICH, so it could be considered a risk marker of hemorrhage. ICH was also associated with baseline variation, male gender and prolonged stay in ICU. Normal standard coagulation tests did not exclude FXIII disorder. Detect on time FXIIID and replacement treatment could become a therapeutic target in future studies.